ANALISIS KEBIJAKAN PEMERINTAH DAN PARTISIPASI MASYARAKAT DALAM UPAYA PENANGGULANGAN ROB (Studi Kasus Kota Tegal) - Ardiansyah, Soni Hazam; Santosa, Edi; Widayati, Wiwik (Journal of Politic and Government Studies, 2013)
Topographically, Tegal city located in low-lying areas in the northern coastal areas of Java Sea. This topographic conditions that led to the city of Tegal has the potential vulnerability of disaster caused by sea water is quite high. The city is faced with the question every year tidal flood. According to Law No. 32 of 2009 in the protection and management of environmental, district / city government duty and authority to determine level of district / city. Tegals city government has a duty to establish appropriate policies in order to rob the response. Development paradigm has gradually shifted its efforts on increasing public participation in various phases of development activities. Principles of the implementation of the program is to put the public other than as objects of development is also a subject or perpetrator of development that is expected to continue / expand the development program and can solve their own problems, especially in improving the quality of settlement environment. Of it is to know how public participation in the prevention rob tegal city.In this study the researchers used a combination of qualitative and quantitative methods (mixed methods design). Mixed methods design is a procedure to collect data, analyze and